A new production route of Gadolinium-148 for use in Radioisotope Thermoelectric Generators. (July 2022) - Artun, Ozan
Abstract: The production of Gd-148 had challenges for available methods in the literature, such as its high cost and low production amount. Therefore, we recommend a new production route of Gd-148 on natural Sm and Eu targets via particle accelerators. For this aim, we calculated and simulated cross-section, activity, the yield of product, and integral yield curves for 21 different nuclear reaction processes under certain conditions. Based on the obtained results, we proposed the radioisotope Gd-148 to use Radioisotope Thermoelectric Generators for deep space and planetary explorations in spacecraft and space-probes as a suitable energy source, instead of Pu-238. Highlights: We recommend a new production route of Gadolinium-148 for use in Radioisotope Thermoelectric Generators. We proposed the radioisotope Gd-148 to use Radioisotope Thermoelectric Generators for deep space and planetary explorations. We recommend nuclear reaction processes for the production of Gd-148.